Patient-reported outcomes after curative treatment for prostate cancer with prostatectomy, primary radiotherapy or salvage radiotherapy - Sælen, Marie Grøn; Hjelle, Line Veronika; Aarsæther, Erling Johan; Knutsen, Tore; Andersen, Sigve; Bentzen, Anne Gry; Richardsen, Elin; Fosså, Sophie Dorothea; Haugnes, Hege Sagstuen (Acta Oncologica, 2023)
Background Trials reporting adverse health outcomes (AHOs) in terms of patient-reported outcome measures (PROMs) after contemporary curative treatment of prostate cancer (PC) are hampered by study heterogeneity and lack of new treatment techniques. Particularly, the evidence regarding toxicities after radiotherapy (RT) with the volumetric arc therapy (VMAT) technique is limited, and comparisons between men treated with surgery, primary radiotherapy (PRT) and salvage radiotherapy (SRT) are lacking. The aim of the study was to evaluate change in PROMs 3 months after treatment with robotic-assisted laparoscopic prostatectomy (RALP), PRT and SRT administered with VMAT. Material and methods A prospective cohort study of men with PC who received curative treatment at the University Hospital of North Norway between 2012 and 2017 for RALP and between 2016 and 2021 for radiotherapy was conducted. A cohort of 787 men were included; 406 men treated with RALP, 265 received PRT and 116 received SRT. Patients completed the validated PROM instrument EPIC-26 before (pre-treatment) and 3 months after treatment. EPIC-26 domain summary scores (DSSs) were analysed, and changes from pre-treatment to 3 months reported. Changes were deemed clinically relevant if exceeding validated minimally clinically important differences (MCIDs). Results Men treated with RALP reported clinically relevant declining urinary incontinence DSS (−41.7 (SD 30.7)) and sexual DSS (−46.1 (SD 30.2)). Men who received PRT reported worsened urinary irritative DSS (−5.2 (SD 19.6)), bowel DSS (−8.2 (SD 15.1)) and hormonal DSS (−9.6 (SD 18.2)). Men treated with SRT experienced worsened urinary incontinence DSS (−7.3 (SD 18.2)), urinary irritative DSS (−7.5 (SD 14.0)), bowel DSS (−12.5 (SD 16.1)), sexual DSS (−14.9 (SD 18.9)) and hormonal DSS (−23.8 (SD 20.9)). Conclusion AHOs 3 months after contemporary curative treatment for PC varied according to treatment modality and worsened in all treatment groups, although most in SRT.